What kind of sustainable development do we need? - Basart, Josep M.; Farr´ús, Mireia; Serra, Montse (Iberoamerican Journal of Development Studies, 2023)
Today, the Sustainable Development Goals (SDGs) are the main framework of reference when addressing sustainability and human development. Unfortunately, there are several aspects and issues that the SDGs have ignored or underestimated and can become serious obstacles to their success. Among them, the ethical, cultural, and spiritual dimensions of human life seem to have faded into oblivion. Without these dimensions, the SDGs may become a kind of well-intended but blind problem-solving strategy that ignores the reasons of the crisis it wants to redress. This absence is apparent when the vocabulary used by the SDGs comes under scrutiny and is still more evident when it is compared with the language used in other well-known international declarations on the same subject. Bringing this shortcoming to light opens the possibility for the SDGs to review the strategies with which they could be more effective when pursuing their purposes in the coming years.
Keywords: sustainable development; Agenda 2030; human development; global crisis; well-being